PROGNOSTIC FACTORS IN THE TREATMENT OF LUNG METASTASES FROM COLORECTAL CANCER - B. B. Akhmedov; M. M. Davydov; M. Yu. Fedyanin; V. A. Aliev; S. S. Gordeev; I. A. Dadyev (Сибирский онкологический журнал)
Based on the results of worldwide clinical studies, survival of colorectal cancer patients with lung metastases is significantly influenced by curative resection, number of metastases and disease free interval. Intrathoracic lymph node metastases in combination with pulmonary metastases as well as the CEA level of greater than 10ng/ml are found to be the most unfavorable prognostic factors. Most studies have found no significant relationship between survival and the size of the primary tumor and unilateral/bilateral distribution of pulmonary metastases. However, some authors consider that bilateral metastasis and T3-4 tumors are unfavorable prognostic factors. The key factors for surgical treatment of pulmonary metastases are the feasibility of performing curative resection and the absence of other manifestations of the disease.